Inflammatory Memory in Chronic Skin Disease - Joseph A. Daccache; Shruti Naik (Elsevier, 2024)
Inflammation is a hallmark of remitting-relapsing dermatological diseases. Although a large emphasis has been placed on adaptive immune cells as mediators of relapse, evidence in epithelial and innate immune biology suggests that disease memory is widespread. In this study, we bring to the fore the concept of inflammatory memory or nonspecific training of long-lived cells in the skin, highlighting the epigenetic and other mechanisms that propagate memory at the cellular level. We place these findings in the context of psoriasis, a prototypic flaring disease known to have localized memory, and underscore the importance of targeting memory to limit disease flares.